Talent selection in 3 × 3 basketball: role of anthropometrics, maturation, and motor performance - Schmitz, T. L.; Fleddermann, M.-T.; Zentgraf, K. (Frontiers in Sports and Active Living, 2024)
Introduction 3 × 3 basketball is becoming more and more professionalized, which is leading to a growing interest in talent development and talent selection. Different studies have demonstrated relevant factors in the talent selection process of 5v5 basketball but not in 3 × 3 basketball. Therefore, this study investigated the main predictors in the talent selection process in 3 × 3 basketball athletes.